Intestinal organoids in inflammatory bowel disease: advances, applications, and future directions - Jianzhen Ren; Silin Huang (Frontiers in Cell and Developmental Biology)
Inflammatory bowel disease (IBD), characterized by chronic gastrointestinal inflammation, is a significant global health challenge. Traditional models often fail to accurately reflect human pathophysiology, leading to suboptimal treatments. This review provides an overview of recent advancements in intestinal organoid technology and its role in IBD research. Organoids, derived from patient-specific or pluripotent stem cells, retain the genetic, epigenetic, and structural characteristics of the native gut, allowing for precise modeling of key aspects of IBD. Innovations in CRISPR editing, organoid-microbe co-cultures, and organ-on-a-chip systems have enhanced the physiological relevance of these models, facilitating drug discovery and personalized therapy screening. However, challenges such as vascularization deficits and the need for standardized protocols remain. This review underscores the need for interdisciplinary efforts to bridge the gap between models and the complex reality of IBD. Future directions include the development of scalable vascularized models and robust regulatory frameworks to accelerate therapeutic translation. Organoids hold promise for unraveling IBD heterogeneity and transforming disease management.